AB0624 The effectiveness of different oral compounds of vitamin D3 on 25-OH vitamin D serum levels in a retrospective longitudinal study of italian SLE patients. (23rd January 2014) - Andreoli, L.; Dall'Ara, F.; Piantoni, S.; Scarsi, M.; Allegri, F.; Tincani, A.
Abstract : Background: Systemic Lupus Erythematosus (SLE) patients (pts) are generally instructed to avoid direct sunlight, since UVB radiations may induce massive apoptosis in the skin and trigger a flare. As a consequence, SLE pts are at risk for low vitamin D (vit.D) levels, being vit.D mostly produced in the skin upon UVB activation. Hypovitaminosis D may be detrimental as it has been shown that Vit.D can have immunomodulatory effects that counteract inflammation. Therefore, adequate vit.D levels may be beneficial in SLE pts. Little is known on the effectiveness of current supplementation strategies with oral vitamin D3, which is generally given to SLE pts as a prophylactic measure against glucocorticoid-induced osteoporosis. Objectives: To evaluate longitudinally 25-OH vit.D levels in SLE pts, in relation to disease activity. Methods: Fifty SLE pts (5 m, 45 f; mean age: 34 years) from a single center in Northern Italy were evaluated at two time-points (winter: november-april, summer: may-october) during clinical remission. Thirty of these pts were also evaluated during a flare. Healthy controls (n=171) from the same area (64 m, 107 f; mean age: 35 years) were also evaluated in different seasons. A total of 301 samples were analyzed for serum 25-OH vit.D with a chemiluminescence assay kindly performed by the manufacturer (DiaSorin, Italy). Comparisons were performed by Mann-Whitney test. Levels above 30 ng/ml were considered as sufficient, according to international guidelines. Results: SLE pts had lower vit.D levels than controls during summer (median 29.4 vs 39.2 ng/ml, p=0.005) but not during winter (26.4 vs 21.6, p=ns). During wintertime, SLE pts were taking either oral vit.D drops (n=24;48%), oral vit.D+calcium compounds (n=12;24%) or no supplementation (n=14;28%). Those on oral drops had significantly higher vit.D levels (32 ng/ml) than those on vit.D+calcium (21 ng/ml) or no supplementation (15, 6 ng/ml) (no difference between the latter two groups). The median weekly dosage was higher for oral drops than for vit.D+calcium (6250 vs 4560 UI, p=0.009). Insufficient vit.D levels were more frequently found during flares (67%) than during remission, both in winter (60%) and in summer (52%). No difference in the dosage of vit.D supplementation was found between flare and remission (p=0, 55). Winter flares were associated with lower vit.D levels in comparison with remission during the same and the opposite season for each patient (21.1 vs 30 vs 33.5 ng/ml, Friedman test). Conclusions: As expected, SLE pts showed lower vit.D levels than healthy controls. More than a half of them had insufficient values, suggesting that current strategies for vit.D supplementation in SLE pts may not be sufficient for reaching levels above 30 ng/ml. Vit.D+calcium compounds seem to be less effective than oral drops, probably because of lower vit.D content and poorer compliance by the patients (heartburns due to calcium). It could be useful to periodically check SLE pts for 25-OH vit.D levels, in order to optimize supplementation. Vit.D repletion throughout the year may be beneficial, especially during winter, the period in which vit.D insufficiency may become critical to the onset of SLE flare. References: Cutolo M, Vitam Horm. 2011, 86:327-51; Holick MF, J Clin Endocrinol Metab 2011, 96:1911–30; Ruiz-Irastorza G, Rheumatology 2008, 47:920-3. Disclosure of Interest: None Declared